2018
DOI: 10.2478/acve-2018-0021
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Characteristics and Expression of Estrogen and Progesterone Receptors in the Canine Endometrium During the Estrus Cycle, Cystic Endometrial Hyperplasia and Pyometra

Abstract: The estrus cycle of bitches is divided into four phases: proestrus, estrus, diestrus and anestrus, during which different morphological changes, and also cyclic changes of estrogen and progesterone receptors are present. Several pathological changes can be differentiated on the endometrium, but one of these is the most important - cystic endometrial hyperplasia, which frequently develops into pyometra. The aim of the present study was to describe morphological characteristics, and expression of estrogen and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
(37 reference statements)
0
2
1
Order By: Relevance
“…Similar to the present study, Misirlioglu et al 8 also observed greater immunostaining of PR in the uterus of cats with pyometra, as was also demonstrated in dogs. 7 However, different from the ERα results of this study, Prapaiwan et al 3 observed a reduction in endometrial immunostaining of ERα in dogs with pyometra, suggesting that there may be species-specific differences in uterine ERα expression in the pyometra condition. Together, our results suggest that the higher uterine gene and protein expression of ERα and PR in cats with pyometra, as well as higher plasma levels of P4, are involved in the pathogenesis of this disease in cats, since the development of pyometra in dogs depends on a prior hyperprogesteronic state.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…Similar to the present study, Misirlioglu et al 8 also observed greater immunostaining of PR in the uterus of cats with pyometra, as was also demonstrated in dogs. 7 However, different from the ERα results of this study, Prapaiwan et al 3 observed a reduction in endometrial immunostaining of ERα in dogs with pyometra, suggesting that there may be species-specific differences in uterine ERα expression in the pyometra condition. Together, our results suggest that the higher uterine gene and protein expression of ERα and PR in cats with pyometra, as well as higher plasma levels of P4, are involved in the pathogenesis of this disease in cats, since the development of pyometra in dogs depends on a prior hyperprogesteronic state.…”
Section: Discussioncontrasting
confidence: 95%
“…In dogs, there is an increase in the uterine expression of P 4 receptors, suggesting that alterations in uterine expression of this receptor are also involved in the pathogenesis of this disease in this animal species. 3 , 7 In cats, on the other hand, studies are scarce. The only study, carried out by Misirlioglu et al, 8 demonstrated that estrogen receptor alpha (ERα) expression was reduced in the uterus of cats with mild endometrial hyperplasia, while there was an increase in progesterone receptor (PR) in cats with mild and severe endometrial hyperplasia.…”
Section: Introductionmentioning
confidence: 99%
“…Although it has already been shown that lower PR scores occur in the dioestrous compared to other phases of the oestrous cycle in bitches (Kunkitti et al, 2011), most studies showed high immunostaining of this receptor in the dioestrous and late dioestrous phases (Marinković et al, 2018;Vermeirsch et al, 2000), which is consistent with our observations. Treatment with vitamin B6, in this sense, induces a reduction in the population of animals in terms of cellular positivity of PR in the deep glands in score '2' and increases, although not significantly, the number of animals in score '3'.…”
Section: Discussionsupporting
confidence: 93%
“…For ERα, in turn, low cell positivity scores in the different treatment groups were observed, perhaps associated with the low expression of this receptor in the dioestrous phase, as observed in other studies in bitches (Kunkitti et al, 2011;Marinković et al, 2018;Ozyurtlu et al, 2010) and queens (de Jesus Nascimento et al, 2023).…”
Section: Discussionsupporting
confidence: 71%
“…In giant anteaters and dogs, uterine background lesions have been found to consist of inflammatory infiltrates in different uterine layers, resulting in endometritis and metritis; moreover, luminal uterine secretion/edema is present, which may be associated with varying phases of the estrus cycle ( 19 21 , 25 – 27 ).…”
Section: Discussionmentioning
confidence: 99%